Electrocatalytic oxidation of ethanol and ethylene glycol on cubic, octahedral and rhombic dodecahedral palladium nanocrystals. Issue 20 (21st February 2018) - Ma, Xian-Yin; Chen, Yafeng; Wang, Han; Li, Qiao-Xia; Lin, Wen-Feng; Cai, Wen-Bin
Abstract : Ethanol and ethylene glycol electrocatalytic oxidation on Pd cubic, octahedral and rhombic dodecahedral nanocrystals in alkaline media was systematically investigated. Abstract : Cubic, octahedral and rhombic dodecahedral Pd nanocrystals were synthesized and examined as nanocatalysts for electro-oxidation of ethanol and ethylene glycol. Combined electrochemical measurements and density functional theory calculations reveal that nanofacet-dependent affinity and reactivity of OHads and COads are closely linked to the C2 alcohol oxidation activities, with the highest reactivity found on the Pd nanocubes bounded by 100 facets.